2020
DOI: 10.1002/rcs.2069
|View full text |Cite
|
Sign up to set email alerts
|

Contact surface area and its association with outcomes in robotic‐assisted partial nephrectomy

Abstract: Background: Renal tumor scoring systems, such as the contact surface area value, aim to assist in predicting outcomes following robotic-assisted partial nephrectomy.The aim of this study is to identify associations between specific postoperative outcomes and the contact surface area of renal masses. Methods:We analyzed 332 consecutive robotic-assisted partial nephrectomies and calculated contact surface area for renal tumors with the contact surface area formula (CSA = 2πrd), where π ≈ 3.14, r = greatest tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that a higher CS is related to a longer warm ischemic time, higher estimated blood loss, longer duration of hospitalization, and decreased renal function. 13 However, to our knowledge, they did not reveal the relationship between the CS and CSE. For tumors showing a large contact area with the renal parenchyma, surgeons set the cutting line of the tumor wider because of the di culty in imaging the tumor depth and concerns regarding a positive surgical margin.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies have reported that a higher CS is related to a longer warm ischemic time, higher estimated blood loss, longer duration of hospitalization, and decreased renal function. 13 However, to our knowledge, they did not reveal the relationship between the CS and CSE. For tumors showing a large contact area with the renal parenchyma, surgeons set the cutting line of the tumor wider because of the di culty in imaging the tumor depth and concerns regarding a positive surgical margin.…”
Section: Introductionmentioning
confidence: 62%
“…In previous reports, a higher CS was associated with a longer warm ischemic time, higher estimated blood loss, longer duration of hospitalization, and decreased renal function. 13 However, considering the lack of studies evaluating the in uence of CS on the occurrence of CSE, we analyzed this in uence by evaluating the relationship between CSE and CS in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that a higher CS is related to a longer warm ischemic time, higher estimated blood loss, longer duration of hospitalization, and decreased renal function. [ 13 ] However, to our knowledge, they did not reveal the relationship between the CS and CSE. For tumors showing a large contact area with the renal parenchyma, surgeons set the cutting line of the tumor wider because of the difficulty in imaging the tumor depth and concerns regarding a positive surgical margin.…”
Section: Introductionmentioning
confidence: 72%
“…In previous reports, a higher CS was associated with a longer warm ischemic time, higher estimated blood loss, longer duration of hospitalization, and decreased renal function. [ 13 ] However, considering the lack of studies evaluating the influence of CS on the occurrence of CSE, we analyzed this influence by evaluating the relationship between CSE and CS in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…15 As more vascularized renal parenchyma is likely to be included in tumors with high RNS (large diameter, hilar, and median polar location), a running suture for kidney reconstruction owes unavoidable risk of compromising intrarenal vascular anatomy. 24,25 Thus, it is reasonable to presume that efforts to preserve any little volume of parenchyma for these tumors are crucial to prevent acute kidney injury or CKD. However, the impact of the dissecting technique seemed relatively small in patients with low complexity tumors, but the difference was statistically significant (-1.1% vs -4.4%, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%